Oral manifestations serve as potential signs of ulcerative colitis: A review - Li, Chunyu; Wu, Yuqi; Xie, Yulang; Zhang, You; Jiang, Sixin; Wang, Jiongke; Luo, Xiaobo; Chen, Qianming (Frontiers in Immunology, 2022)
As an immune dysregulation-related disease, although ulcerative colitis (UC) primarily affects the intestinal tract, extraintestinal manifestations of the disease are evident, particularly in the oral cavity. Herein, we have reviewed the various oral presentations, potential pathogenesis, and treatment of oral lesions related to UC. The oral manifestations of UC include specific and nonspecific manifestations, with the former including pyostomatitis vegetans and the latter encompassing recurrent aphthous ulcers, atrophic glossitis, burning mouth syndrome, angular cheilitis, dry mouth, taste change, halitosis, and periodontitis. Although the aetiology of UC has not been fully determined, the factors leading to its development include immune system dysregulation, dysbiosis, and malnutrition. The principle of treating oral lesions in UC is to relieve pain, accelerate the healing of lesions, and prevent secondary infection, and the primary procedure is to control intestinal diseases. Systemic corticosteroids are the preferred treatment options, besides, topical and systemic administration combined with dietary guidance can also be applied. Oral manifestations of UC might accompany or precede the diagnosis of UC, albeit with the absence of intestinal symptoms; therefore, oral lesions could be used as good mucocutaneous signs to judge the occurrence and severity of UC, thus facilitating the early diagnosis and treatment of UC and avoiding severe consequences, such as colon cancer.